2021
DOI: 10.1530/eje-20-1088
|View full text |Cite
|
Sign up to set email alerts
|

Corticotroph tumor progression after bilateral adrenalectomy (Nelson’s syndrome): systematic review and expert consensus recommendations

Abstract: BACKGROUND: Corticotroph tumor progression (CTP) leading to Nelson’s syndrome (NS) is a severe and difficult-to-treat complication subsequent to bilateral adrenalectomy (BADX) for Cushing’s disease. Its characteristics are not well described, and consensus recommendations for diagnosis and treatment are missing. METHODS: A systematic literature search was performed focusing on clinical studies and case series (≥5 patients). Definition, incidence, treatment and long-term outcomes of CTP/NS after BADX were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 103 publications
2
28
0
7
Order By: Relevance
“…Three of these studies found that high ACTH concentrations one year after BA [49,52,53] were associated with pituitary tumor progression. Thus, these findings support the suggestion that ACTH should be monitored following BA in patients with CD [54,55].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Three of these studies found that high ACTH concentrations one year after BA [49,52,53] were associated with pituitary tumor progression. Thus, these findings support the suggestion that ACTH should be monitored following BA in patients with CD [54,55].…”
Section: Discussionsupporting
confidence: 85%
“…*additional data. Abbreviations: Surgery, pituitary surgery prior to bilateral adrenalectomy [55]. Furthermore, the authors recommend active surveillance with MRI three months after BA, and every 12 months for the first 3 years, and every 2-4 years thereafter, based on clinical findings.…”
Section: Discussionmentioning
confidence: 99%
“…Corticotroph tumor progression (CTP) leading to Nelson’s syndrome (NS) is characterized by hyperpigmentation and an increase in tumor size in patients with refractory CD submitted to bilateral adrenalectomy (BA); tumor growth can be dramatic with severe complications including death [ 62 ]. To date, no effective predictive factors are available to a priori identify patients at high risk of developing NS, and the only option is the close post-operative monitoring of all patients [ 62 ].…”
Section: Gr Mutation and Clinical Phenotypementioning
confidence: 99%
“…Pituitary radiotherapy is an additional treatment option for CD but can take months to years to lower cortisol production. Bilateral adrenalectomy (BLA) provides immediate, reliable correction of hypercortisolism but mandates life-long corticosteroid replacement therapy, and, in patients with CD, may be complicated by corticotroph tumor progression syndrome in 25–40% of patients[ 14 ].…”
Section: Introductionmentioning
confidence: 99%